Psychopathology in Pediatric Epilepsy: Role of Antiepileptic Drugs - Caplan, Rochelle (Frontiers in Neurology, 2012)
Children with epilepsy are usually treated with antiepileptic drugs (AEDS). Some AEDs adversely affect behavior in susceptible children. Since psychiatric comorbidity is prevalent in pediatric epilepsy, this paper attempts to disentangle these AED side effects from the psychopathology associated with this illness. It first outlines the clinical and methodological problems involved in determining if AEDs contribute to the behavior and emotional problems of children with epilepsy. It then presents research evidence for and against the role AEDs play in the psychopathology of children with epilepsy, and outlines how future studies might investigate this problem. A brief description of how to clinically separate out AED effects from the complex illness-related and psychosocial factors that contribute to the behavior difficulties of children with epilepsy concludes the paper.